Pengaruh Gaya Kepemimpinan Transaksional dan Motivasi Kerja Terhadap Kinerja Guru di Sma Negeri 6 Palembang - Putri, Melia Sari Onika; Alie, Juhaini; Roswaty (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze and determine the effect of Transactional Leadership style and work motivation on teacher performance at SMA Negeri 6 Palembang. The Transactional Leadership style emphasizes reciprocal relationships between leaders and subordinates through a system of rewards and supervision, while work motivation serves as the primary driving force influencing teacher productivity. A quantitative approach was used in this study, with primary data collected through questionnaires and interviews. The sample consisted of 75 teachers at SMA Negeri 6 Palembang. Data analysis was conducted using SPSS V27 software, which included validity and reliability tests, classical assumption tests, multiple regression analysis, and hypothesis testing. Based on the t-test results, both transactional leadership style and work motivation have a positive and significant effect on teacher performance, with a significance value of 0.001 < 0.05. Furthermore, based on the F-test results, both transactional leadership style and work motivation simultaneously have a significant effect on teacher performance at SMA Negeri 6 Palembang, with a significance value of 0.00 < 0.05.